PENYIDIKAN EFEK SAMPING HALOPERIDOL DAN CHLORPROMAZINE : STUDI KASUS PADA PASIEN RAWAT INAP RUMAH SAKIT JIWA DAERAH Dr. AMINO GONDOHUTOMO SEMARANG PERIODE 2005 - sri susilowati (Universitas Wahid Hasyim Semarang, 2007)
ABSTRACTHaloperidol and chlorpromazine antipsycotic were used for broad and so long time. That drugs used could shown undesire side effect. Objective of this study was to investigate haloperidol and chlorpromazine side effect, especially was to know relative risk (RR) of extrapiramidal and hypotension orthostatic side effects of haloperidol and chlorpromazine antipsycotic used in Dr. Aminogondohutomo Mental Hospital durimg 2005. Non experimental, retrospective and Case Control study design was done. Population of this study was patient ward in Dr. Aminogondohutomo Mental Hospital durimg 2005. Data was taken retrospectively from medical record. Analytical of data used Chi Kuadrat and Odds Ratio (OR) was to know relative risk (RR) of extrapiramidal and hypotension orthostatic side effects of haloperidol and chlorpromazine antipsycotic used. The results showed there were 27,17% extrapiramidal side effects of haloperidol used and 15,24 % hypotension orthostatic side effects of chlorpromazine used. That were the first rank of side effect in every that antipsycotic.The value of relative risk (RR) of extrapiramidal side effects of haloperidol used was 5 and 3 for hypotension orthostatic side effects of chlorpromazine used. That meaned patient who used haloperidol could 5 more time got extrapiramidal side effects than haloperidol unused and patient who used chlorpromazine could 3 more time got hypotension orthostatic side effects than chlorpromazine unused. Keyword : Extrapiramidal and hypotension orthostatic side effects, haloperidol and chlorpromazine antipsycotic, , Dr. Aminogondohutomo Mental Hospital